17 Real-world experience and outcomes after device-led patent foramen ovale closure. (17th July 2020) - Khan, Usman Azhar; Brennan, Paul; Lockhart, Christopher; Owens, Colum; Spence, Mark
Abstract : Aims: A patent foramen ovale (PFO) is a common defect that affects up to 34% of the population. Recent evidence has emerged supporting PFO closure in the event of cryptogenic ischaemic stroke, transient ischaemic attack (TIA), systemic embolism and migraine. We aimed to report real-world experience and outcomes for all consecutive patients that had PFO closure in our hospital between March 2009 and October 2019. Methods: We retrospectively analysed baseline clinical characteristics, indications for PFO closure, procedural characteristics and long-term clinical follow-up using our dedicated hospital database and Northern Ireland Electronic Care Record. Results: PFO closure was performed in 133 patients between March 2009 and October 2019. 59 (44%) of cases were performed between 2009-2016 with 74 (56%) cases performed between 2017-2019, coinciding with the publication of supporting randomized control trials. The mean patient age was 43 ±15 years and 69 (52%) patients were female. 16 (12.1%) of patients had a history of systemic hypertension, 4 (3%) diabetes mellitus and 35 (26%) had a smoking history. Only one patient had a thrombophilia diagnosis. Cerebrovascular events including ischaemic stroke and TIA's were the leading indication for PFO closure in 123 (92.5%) cases. Systemic embolism, platypnea-orthodeoxia syndrome and decompressive illness were the indications in 4 (3%), 2 (1.5%) and 1(0.75%) case(s), respectively. 'Other' indications made up the remaining 3 patients. The majority of procedures were performed under general anaesthetic (GA) in 129 (97%) cases. All cases were performed using trans-oesophageal echocardiography guidance. The mean procedure time was 38 ± 23minutes and the mean size of percutaneous device used was 25mm. Gore (52%) and Amplatzer (35%) septal occluders were the most commonly used devices. There were no procedural deaths. Cardiac tamponade, major vascular injury, pulmonary embolism and/or device embolism did not occur in any patient. Only one patient had a new arrhythmia (atrial fibrillation (AF)) during the periprocedural period. The median length of stay was 1day. Antithrombotic data at discharge was available for 129 (97%) patients. The main antithrombotic strategy adopted was dual antiplatelets in 112 (87%) cases, single antiplatelet in 10 (8%) cases and oral anticoagulation +/- a single antiplatelet made up the remainder of cases, respectively. No patients were readmitted to hospital for bleeding events on interrogation of NIECR. The median follow-up duration after PFO closure was 31 months (range 2-1439months). 3 patients suffered a recurrent neurological event during follow-up, giving an event rate of 0.6/100 patient-years (PY). Infective endocarditis was not observed for any patients. 5 (3.8%) patients had a diagnosis of new AF or atrial flutter during follow-up, all of which occurred within three months of the procedure. 3 patients (2.3%) died during follow-up (median age 56 years (20-75years)) but all of these deaths were non-cardiac in nature. Conclusions: PFO closure was performed safely in our hospital with a very low rate of procedural complications. New arrhythmias and cerebrovascular events occurred in a low proportion of the population. Our real-world outcomes in combination with the previously published major randomized control trials supports the continued application of device-led PFO closure in patients with cryptogenic ischaemic stroke, TIA and/or systemic embolism. Conflict of Interest: none